2021
DOI: 10.1016/j.ejim.2021.01.021
|View full text |Cite
|
Sign up to set email alerts
|

Venous lactate improves the prediction of in-hospital adverse outcomes in normotensive pulmonary embolism

Abstract: Background: Arterial lactate is an established risk marker in patients with pulmonary embolism (PE). However, its clinical applicability is limited by the need of an arterial puncture. In contrast, venous lactate can easily be measured from blood samples obtained via routine peripheral venepuncture. Methods: We investigated the prognostic value of venous lactate with regard to in-hospital adverse outcomes and mortality in 419 consecutive PE patients enrolled in a single-center registry between 09/2008 and 09/2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 23 publications
0
8
0
1
Order By: Relevance
“…Ebner et al discovered that the adjust venous lactate cut-off value can increase the risk of poor in-hospital endpoints in patients with acute PE, while the lactate value exceeding 3.3 mmol/L was a strong predictor of both in-hospital adverse outcome and overall death. 21 Therefore, given the latent risk of arterial puncture, peripheral venous lactate may be a promising form and need further external validated the optimal cut-off value.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ebner et al discovered that the adjust venous lactate cut-off value can increase the risk of poor in-hospital endpoints in patients with acute PE, while the lactate value exceeding 3.3 mmol/L was a strong predictor of both in-hospital adverse outcome and overall death. 21 Therefore, given the latent risk of arterial puncture, peripheral venous lactate may be a promising form and need further external validated the optimal cut-off value.…”
Section: Discussionmentioning
confidence: 99%
“…Three of the included studies were prospective, the others were retrospective design. Lactate concentrations were obtained from venous blood sampling in two studies, 20,21 while four studies 13,[17][18][19] evaluated arterial lactate levels. Five studies used 2 mmol/L as a cut-off value, while one study had a venous lactate cut-off value of 3.3 mmol/L.…”
Section: Characteristics Of Included Studiesmentioning
confidence: 99%
“…In the same vein, lactate assessment is highly appreciated in intensive care units (ICUs), where an abnormal level is a beacon of meaningful information of the current and future status of the patient. In this sense, it is possible to relate it with situations such as haemorrhagic shock, pulmonary embolism, cardiogenic shock, respiratory poisoning and renal failure, among others [ 8 , 9 , 10 , 11 , 12 , 13 ]. Moreover, alternative studies pointed out the existence of abnormal lactate concentration in cancer cells during metastases [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, Ebner and colleagues proposed adding the easily obtained venous lactate levels above a higher cutoff, defined as > 3.3 mmol/l, to the 2019 ESC stratification protocol and found that this results in increased sensitivity and specificity in adverse outcome and mortality prediction in the intermediate-high risk subgroup of patients. The proposed higher than previously suggested cutoff may be in part explained by physiologically occurring slight differences in lactate concentrations between venous and arterial blood [45]. Finally, Ebner et al also investigated whether the subgroup of high-risk PE clinically presenting as obstructive shock could be better defined in terms of end-organ perfusion and mortality with lactate measurement, reporting that patients with levels above 3.8 mmol/l were characterized by higher mortality and that applying this improved risk stratification [46].…”
Section: Further Laboratory Biomarkersmentioning
confidence: 70%